Forest stratification utilization by Sulawesi crested black macaques during daily activities at Tangkoko-Batuangus Nature Reserve, North Sulawesi, Indonesia. - Saroyo Sumarto (School of Industrial Technology, Universiti Sains Malaysia, 2014)
Forest stratification refers to the different layers of plants in a forest. In a mature forest, there are typically several distinct layers of vegetation rising from. the forest floor to the tree canopy. This research, which conducted at Tangkoko-Batuangus Nature Reserve from October 2006 to January 2007, focused on utilization of five stratification of tropical rain forest by crested black Macaques (Macaca nigra) during the daily activities of the species. Data were collected from. two habituated groups called Rambo Group I and Rambo Group 11 Total samples were 21 individual of Rambo Group I and 17 individuals of Rambo Group II. Daily activities ranged from. feeding, foraging, moving, resting, and social interaction that collected by focal animal sampling with 2-minute intervals.Forest was divided vertically into Slayers namely Layer-A (40-50 m), Layer-B (18-39 m), Layer-C (4-17), Layer-D(1-3m),and Layer E (0-1 m). Total observation was 12,829 in Rambo Group I and 12,609 in Rambo Group II.Forest stratification utilization and daily activities of Rambo I and Rambo II were not significantly affected by the habitat characteristic even through each group has different home range. Home range of Rambo Group I was Dominated by primary forest whereas home range of Rambo Group II was dominated by secondary forest and shrub.